2022
DOI: 10.3389/fimmu.2022.1088606
|View full text |Cite
|
Sign up to set email alerts
|

Tear-derived exosomal biomarkers of Graves’ ophthalmopathy

Abstract: Graves’ ophthalmopathy (GO), the most frequent extrathyroidal manifestation of Graves’ disease (GD), can lead to a significant decline in the quality of life in patients. Exosomes, which contain proteins, lipids and DNA, play important roles in the pathological processes of various diseases. However, their roles in Graves’ ophthalmopathy are still unclear. We aimed to isolate exosomes and analyze the different exosomal proteins. Tear fluids were collected from twenty-four GO patients, twenty-four GD patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A more recent study from 2022 reported that patients with GD and active TED had elevated levels of caspase-3, complement C4A, and apolipoprotein A-IV, compared with those without TED. 73 Caspase-3 has been related to apoptosis. Complement C4A (from the classic complement pathway) is essential in local inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study from 2022 reported that patients with GD and active TED had elevated levels of caspase-3, complement C4A, and apolipoprotein A-IV, compared with those without TED. 73 Caspase-3 has been related to apoptosis. Complement C4A (from the classic complement pathway) is essential in local inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…72 A more recent study from 2022 reported that patients with GD and active TED had elevated levels of caspase-3, complement C4A, and apolipoprotein A-IV, compared with those without TED. 73 Caspase-3…”
Section: Components Of Inflammation and Immunitymentioning
confidence: 99%
“…One such challenge is the requirement for distinct processing procedures for EV samples derived from different body fluids (Figure 3 ) 30 . EVs are demonstrated that presented in almost all the body fluids including cell culture-conditioned media 31 - 35 , blood/serum/plasma 36 - 40 , pleural effusions and ascites 41 - 44 , saliva 45 - 48 , urine 49 - 55 , tear fluid 56 - 59 , and cerebrospinal fluid (CSF) 60 - 63 . The concentration, composition, and bioactivities of EVs can vary significantly depending on the type of body fluid, collection strategies, storage conditions, and pretreatment methods 64 , 65 .…”
Section: From Biogenesis To Characterization Of Extracellular Vesiclesmentioning
confidence: 99%
“…These findings underscore the potential involvement of tear exosomes in the pathogenesis of GO, marked by elevated levels of cytokines such as IL-1β, IL-8 and IL-13, as well as notable proteins like Caspase-3, C4A and APOA-IV. 11 There is a compelling association between tear exosomes and the pathogenesis of Herpes Stromal Keratitis induced by Herpes Simplex Virus-1. Corneal exosomal microRNA proteins finely tune the response to bacterial infection by influencing corneal innervation and innate immunity.…”
mentioning
confidence: 99%